Debt close to retirement and its implications for retirement well-being - Annamaria Lusardi; Olivia S. Mitchell; Noemi Oggero (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
We analyze debt and debt management of Americans nearing retirement age. We show that older people have numerous financial obligations that can lead to financial distress. Using data from the 2015 National Financial Capability Study and an extensive literature review, we show that lack of financial literacy, lack of information, and behavioral biases help explain the prevalence of debt later in life. Our evidence indicates that debt at older ages can negatively influence retirement well-being.
urn:nbn:de:hebis:30:3-515232
Keywords: 330